2021
DOI: 10.1002/ange.202017126
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Activated Dimagnesium(I) Compounds: Reagents for the Reduction and Selective C−H Bond Activation of Inert Arenes

Abstract: The photochemical activation of dimagnesium(I) compounds, and subsequent high yielding, regioselective reactions with inert arenes are reported. Irradiating benzene solutions of [{(ArNacnac)Mg}2] (ArNacnac=[HC(MeCNAr)2]−; Ar=2,6‐diisopropylphenyl (Dip) or 2,4,6‐tricyclohexylphenyl (TCHP)) with blue or UV light, leads to double reduction of benzene and formation of the “Birch‐like” cyclohexadienediyl bridged compounds, [{(ArNacnac)Mg}2(μ‐C6H6)]. Irradiation of [{(DipNacnac)Mg}2] in toluene, and each of the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Indeed, it has been reported that transient magnesium(I) radicals can doubly reduce and C-H activate arenes such as benzene and toluene. 26,27 Scheme 2. Synthesis of compounds 2 -4 (R = CH2(SiMe3)).…”
Section: Magnesium P-terphenyl Bis(anilide) Complexesmentioning
confidence: 99%
“…Indeed, it has been reported that transient magnesium(I) radicals can doubly reduce and C-H activate arenes such as benzene and toluene. 26,27 Scheme 2. Synthesis of compounds 2 -4 (R = CH2(SiMe3)).…”
Section: Magnesium P-terphenyl Bis(anilide) Complexesmentioning
confidence: 99%
“…These species are the result of a fast C-F bond activation of fluorobenzene, an unprecedented result with heterobimetallic Zn-Al systems that does not occur with Zn/Ga, Mg/ Al or Ca/Al metal pairs. 59,[212][213][214][215] The authors speculated about the possibility of an intermediate species featuring a Zn-Al bond as they were able to isolate and characterise the corresponding Zn-Ga analogue. Nonetheless, computational studies indicate that C-F bond activation does not proceed through a previously formed heterobimetallic complex.…”
Section: Zincmentioning
confidence: 99%